Effect of Foliar Molybdenum Application on Seed Quality of Soybean Cultivars - Cardoso, Bruna Miguel; Lazarini, Edson [UNESP]; Moreira, Adonis; Moraes, Larissa A. C.; Santos, F. L. D. [UNESP]; Dameto, Larissa Sartori (Taylor & Francis Inc, 2020)
Molybdenum (Mo) is an essential micronutrient involved in several biochemical reactions that influence biological nitrogen fixation (BNF). Plants are known to require less molybdenum. The objective of this study was to evaluate the effect of Mo foliar application on four soybean cultivars (Glycine max [L.] Merrill) and their physiological qualities, crude protein, and lipid content. The experimental design was completely randomized, in a 4 x 3 factorial arrangement, with four replicates. Three Mo application rates (0, 400, and 800 g ha(-1)) were used for the AS 3730 IPRO, Bonus IPRO, Desafio RR, and BMX Potencia RR cultivars during their R3 and R5 reproductive stages. The Mo concentration, nutritional parameters (crude protein [CP] and lipids), and physiological quality (electrical conductivity, vigor, aging seed, and germination) of the seeds were then evaluated. The cultivars x Mo application rate interaction had no significant effect. There was an observed increase in Mo content with molybdic leaf fertilization. The BMX Bonus IPRO and BMX Potencia RR cultivars had the best response, with increased Mo concentration within the seeds. The Mo rates did not influence CP and lipids. However, the soybean cultivar x Mo application rate interaction significantly affected the germination percentage and percentage of accelerated aging seeds.
Keywords: Glycine max; crude protein; lipids; vigor; germination; electrical conductivity